FUZZY LOGIC MODELING OF ACID MINE WATER USING GEOCHEMICAL PARAMETERS - Ardiawan; Tedy Agung Cahyadi; Rika Ernawati (Jurnal Scientia, 2023)
Mining activities have the potential to damage the environment, one of the negative impacts of mining activities is the contamination of acid mine water in the Sengklami River. The purpose of this study was to analyze the content of acid mine drainage in the Sengklami River on geochemical parameters based on values, namely pH, Fe, Mn, TSS , BOD, COD, DO, and Sulfides so that they are identified in the Sengklami River. The method used is fuzzy logic modeling of min-max values with primary data so that it can be processed in the form of input data which becomes a fuzzification of the range variable (rule base) which produces a fuzzy inference system and then defuzzifies the fuzzy output data which produces the AAT index value so that the value can be determined. classification of environmental pollution conditions consisting of 3 (three) categories namely mild, moderate and severe. From the test results of 8 parameters pH, Fe, Mn, TSS, BOD, COD, DO and Sulfide, the downstream data for 2020 showed a heavy classification with an AAT index of 0.10, while upstream in 2020 there was also a heavy classification with an AAT index of 0.90. The fuzzy logic model for downstream data for 2022 has a heavy classification with an acid mine water index of 0.03 while upstream in 2022 there is also a heavy classification with an acid mine water index of 0.97. Based on data taken in 2020 and 2022, it can be concluded that the characteristics of pollution are in the upstream and downstream of the river, this condition causes clouding by looking at the acid mine drainage index with a heavy classification.